East as a cultural trend - V. S. Gritsenko, (Ukrainian Cultural Studies, 2021)
The article is devoted to one of the most complex phenomena of the dialectic of cultural development – individual spiritual identification through the selection and development of individual components of a foreign cultural spiritual resource, in this case – the traditional cultures of China and Japan.Contrary to its predominantly factual scientific consideration in the context of issues of cultural borrowing, "spiritual migration" to the East is analyzed as a stable trend, which has its source in the essential intentions of man, remaining not only constant in the centuries-old past of mankind, but also inescapable in its further cultural movement. In this context, the author considers the historical manifestations of heightened interest in the treasures of the Far Eastern cultural area, its transformation from a simple admiration for exotics to confessing the philosophical and worldview guidelines presented by them. The phenomenon of the cultural trend studied in this way, having demonstrated its ability to identify and preserve spiritual recreation, is revealed in its direct connection with the dialectical processes of the cultural development of mankind.In culturology, fashion and the processes of trend formation belong to the issues of the essential series, because they reveal a person's constant desire for change motivated by self-development. According to historical evidence, the orbit of fashion as a way of cultural identification includes not only material and procedural phenomena, but also cultural and ideological complexes with their own model of worldview and behavioral regulations. The emphasis on them arises from the needs of personal self-identification, problematized by the circumstances of personal or public life. The motive for such a choice is the search for a spiritual optimum conducive to self-realization and inner freedom of self-expression. Its absence forms compensatory "trend nodes", the appearance of which is thus predictable, as well as the resource needed to meet this cultural demand. It is at the disposal of cultures formed on the basis of philosophical and worldview universals that consider man as a significant unit of the universe. Some of them are gone, but the cultural memory of mankind preserves the memory of their legacy left to intellectuals. The existing traditional cultures, which for thousands of years nurtured their spiritual core, becoming a Mecca for the spiritually thirsty, have the integral effectiveness of the resource.
Keywords: Far Eastern cultural area, foreign cultural spiritual resource, cultural trend, spiritual self-identification, accent socio-cultural requests, spiritual migration, compensatory "trend nodes"